CPA examination reviewer in auditing problems - Cabrera, Ma. Elenita Balatbat; Cabrera, Gilbert Anthony B. (Manila, Philippines : GIC Enterprises & Co. Inc., 2018)
This provides a competitive advantage by improving the effectiveness of the reader's study time through learning and understanding.
1. Overview of Independent Financial Audit -- 2. Audit of the Revenue and Receipt Cycle -- 3. Audit of the expenditure and Disbursements cycle -- 4. Audit of the production and inventory warehousing cycle -- 5. Audit of the Investing and Financing Cycle -- 6. Substantive Audit of cash -- 7. Substantive Audit of receivables -- 8. Substantive Audit of Investments in Debt/ Equity Financial Instruments -- 9. Substantive Audit of property, plant and Equipment -- 10. Substantive Audit of Intangible Assets -- 11. Substantive Audit of prepaid expenses and deferred charges -- 12. Substantive Audit of other Non current Investments -- 13. Substantive Audit of Liabilities -- 14. Substantive audit of owners equity -- 15. Substantive Audit of revenue and expenses -- 16. Audit of Financial Statements -- 17. Completing the Audit and Report Preparation -- 18. Comprehensive auditing problems.
Keywords: AUDITING -- EXAMINATIONS